Complex genetic control of lung tumorigenesis in resistant mice strains. Issue 11 (6th October 2017) - Dassano, Alice; Pintarelli, Giulia; Cotroneo, Chiara E.; Pettinicchio, Angela; Forcati, Elena; De Cecco, Loris; Borrego, Andrea; Colombo, Francesca; Dragani, Tommaso A.; Manenti, Giacomo
Abstract : The SM/J mouse strain is resistant to chemically‐induced lung tumorigenesis despite having a haplotype, in the pulmonary adenoma susceptibility locus ( Pas1 ) locus, that confers tumor susceptibility in other strains. To clarify this inconsistent genotype‐phenotype correlation, we crossed SM/J mice with another resistant strain and conducted genome‐wide linkage analysis in the (C57BL/6J × SM/J)F2 progeny exposed to urethane to induce lung tumors. Overall, >80% of F2 mice of both sexes developed from 1 to 20 lung tumors. Genotyping of 372 F2 mice for 744 informative non‐redundant SNPs dispersed over all autosomal chromosomes revealed four quantitative trait loci (QTLs) affecting lung tumor multiplicity, on chromosomes 3 (near rs13477379), 15 (rs6285067), 17 (rs33373629) and 18 (rs3706601), all with logarithm of the odds (LOD) scores >5. Four QTLs modulated total lung tumor volume, on chromosome 3 (rs13477379), 10 (rs13480702), 15 (rs6285067) and 17 (rs3682923), all with LOD scores >4. No QTL modulating lung tumor multiplicity or total volume was detected in Pas1 on chromosome 6. The present study demonstrates that the SM/J strain carries, at the Pas1 locus, the resistance allele: a finding that will facilitate identification of the Pas1 causal element. More generally, it demonstrates that lung tumorigenesis is under complex polygenic control even in a pedigree with low susceptibility to this neoplasia, suggesting that the genetics of lung tumorigenesis is much more complex than evidenced by the pulmonary adenoma susceptibility and resistance loci that have, so far, been mapped in a small number of crosses between a few inbred strains. Abstract : Inbred strains of mice, with high or low susceptibility to a certain cancer, are bred together to study how genetics influences cancer in their offspring. Using this method, we previously identified a genetic region called Pas1 that controlled lung tumor formation in mice treated with the chemical urethane. Further research showed that several inbred strains with high susceptibility (e.g., A/J) to lung cancer had similar genetic features at Pas1. Strangely, however, SM/J mice had apparently the same Pas1 features but were resistant. To resolve this conflict, we crossed SM/J and with another resistant strain (C57BL/6J) and exposed the offspring to urethane. Surprisingly, most progeny formed tumors. Analysis of their DNA revealed other chromosomal regions involved in tumor formation. Importantly, it also revealed that Pas1 regions in SM/J and A/J mice were not identical, but had fine genetic differences that could explain the stark differences in tumor susceptibility of the two strains; this finding will help us identify the DNA sequence within Pas1 that actually confers lung cancer susceptibility. Altogether, our research shows that the genetics of lung cancer in mice is more complex than previously thought, suggesting that, in humans too, the risk of lung cancer is more complex than shown so far by genetic studies.